Relationship between health literacy and COVID-19 knowledge: A cross-sectional study - Tao, Zhenbo; Xu, Qianqian; Zhu, Yingying; Mei, Qiuhong; Feng, Hongwei; Jin, Qiuyan; Ding, Shige; Dong, Ying (Frontiers in Public Health, 2023)
Background Health literacy (HL) is a protective factor for some chronic diseases. However, its role in the Coronavirus Disease 2019 (COVID-19) pandemic has not been clarified. This study aims to explore the association between HL and COVID-19 knowledge among residents in Ningbo. Methods A total of 6,336 residents aged 15–69 years in Ningbo were selected by multi-stage stratified random sampling method. The “Health Literacy Questionnaire of Chinese Citizens (2020)” was used to evaluate the relationship between COVID-19 knowledge and HL. Chi-square test, Mann-Whitney U test and logistic regression were used to analyze the data. Results The HL and COVID-19 knowledge levels of Ningbo residents were 24.8% and 15.7%, respectively. After adjusting for confounding factors, people with adequate HL were the more likely to have adequate COVID-19 knowledge compared with those with limited HL (OR = 3.473, 95% CI = 2.974–4.057, P <0.001). Compared with the limited HL group, the adequate HL group had a higher rate of COVID-19 knowledge, a more positive attitude, and a more active behavior. Conclusion COVID-19 knowledge is significantly associated with HL. Improving HL may influence people's knowledge about COVID-19, thereby changing people's behaviors, and finally combating the pandemic.